2022
DOI: 10.3389/fcimb.2022.940687
|View full text |Cite
|
Sign up to set email alerts
|

Bile reflux alters the profile of the gastric mucosa microbiota

Abstract: BackgroundBile reflux can cause inflammation, gastric mucosa atrophy, and diseases such as stomach cancer. Alkaline bile flowing back into the stomach affects the intragastric environment and can alter the gastric bacterial community. We sought to identify the characteristics of the stomach mucosal microbiota in patients with bile reflux.MethodsGastric mucosal samples were collected from 52 and 40 chronic gastritis patients with and without bile reflux, respectively. The bacterial profile was determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
4
2
2
Order By: Relevance
“…The microbial compositional comparison using beta-diversity analysis also showed significant differences according to BR, histological phenotype, and H. pylori infection, although no significant differences were observed between grades in the same categories (i.e., BR1 vs. BR2; LGD vs. EGC). Our results were inconsistent with previous studies that showed no difference in the beta diversity in the gastric mucosal microbiota between patients with and without BR [ 19 , 20 ]. As we discussed the inconsistent results for the effect of H. pylori infection on α-diversity between mucosal samples and gastric juice samples [ 19 , 20 ], we speculate that the effects of BR could also differ between gastric juice and mucosal samples.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The microbial compositional comparison using beta-diversity analysis also showed significant differences according to BR, histological phenotype, and H. pylori infection, although no significant differences were observed between grades in the same categories (i.e., BR1 vs. BR2; LGD vs. EGC). Our results were inconsistent with previous studies that showed no difference in the beta diversity in the gastric mucosal microbiota between patients with and without BR [ 19 , 20 ]. As we discussed the inconsistent results for the effect of H. pylori infection on α-diversity between mucosal samples and gastric juice samples [ 19 , 20 ], we speculate that the effects of BR could also differ between gastric juice and mucosal samples.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results were inconsistent with previous studies that showed no difference in the beta diversity in the gastric mucosal microbiota between patients with and without BR [ 19 , 20 ]. As we discussed the inconsistent results for the effect of H. pylori infection on α-diversity between mucosal samples and gastric juice samples [ 19 , 20 ], we speculate that the effects of BR could also differ between gastric juice and mucosal samples. In addition, the previous study showed significant microbial community differences according to the histology [ 9 ], whereas our study showed no microbial community difference between EGC and LGD.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The reflux of alkaline bile into the stomach can obviously change the gastric environment and shape the composition of gastric microbiota. For example, Huang et al ( 2022 ) observed 92 patients with CG and found that patients with CAG accompanied by bile reflux had higher microbial diversity and richness than those in non-atrophic gastritis patients without bile reflux (Huang et al, 2022 ). However, our results showed induced richness of gastric microbiota in the GIM rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a marked difference in the microbiota structure between patients with and without bile reflux. 59 Excessive methylation can lead to adverse consequences, such as suppressing latent-phase genes, transitioning to the lytic phase, and silencing tumor suppressor genes. In the process, the above factors induce local triggering of the host immune responses and make a difference in lymph node metastasis and the prognosis of EBVaGC.…”
Section: ) Microbiotamentioning
confidence: 99%